Effect of Carburization Parameters on Hardness of Carburized Steel Using MOORA Approach - Hussein, Abbas Khammas; Abbas, Laith Kais; Hameed, Asraa Kareem (Al-Khwarizmi Engineering Journal, 2018)
In this research, (MOORA) approach based– Taguchi design was used to convert the multi-performance problem into a single-performance problem for nine experiments which built (Taguchi (L9) orthogonal array) for carburization operation. The main variables that had a great effect on carburizing operation are carburization temperature (oC), carburization time (hrs.) and tempering temperature (oC). This study was also focused on calculating the amount of carbon penetration, the value of hardness and optimal values obtained during the optimization by Taguchi approach and MOORA method for multiple parameters. In this study, the carburization process was done in temperature between (850 to 950 ᵒC) for 2 to 6 hours. Quenching was done for the specimens after heat treatments in furnace chamber by using different quench solutions, water, salt and polyvinyl alcohol. Analysis of variances - (ANOVA) were performed for nine experiments in order to optimize the problem that was associated with multiple criteria (parameter) to achieve maximum hardness and depth penetration. The program results showed that the optimum conditions are carburization temperature (950 oC), carburization time (2 hrs.), tempering temperature (200oC), tempering time (10 hrs.), and activator (10 wt. %). Furthermore, the best quenching media was the polyvinyl alcohol.